Aspek Finansial Usaha Perikanan Pancing (Long Line) Di TPI Hamadi Kota Jayapura (Studi Kasus: Nelayan Kelurahan Hamadi) - Kalvin Paiki; Kristhopolus K. Rumbiak; Maklon Warpur (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2021)
Hamadi Fish Landing Base (Pengkalan Pendaratan Ikan; TPI Hamadi) is the largest in Papua Province. Most fishermen in TPI Hamadi are long line fishermen. Long line is a fishing gear used to catch pelagic and demersal fish. The purpose of this study is to determine the feasibility of analyzing the business from the financial aspect of the fishing business (long line) at the Hamadi Fish Auction Place (Tempat Pelelangan Ikan; TPI Hamadi) Jayapura City. Data collection methods in this study are the observation method, interview method, documentation method, data analysis related to the financial aspects of the business which include; NPV (Net Present Value), PP (Payback Period) and B/C Ratio (Benefit Cost Ratio). The technical aspects of catching include basic longline fishing gear, operating methods and catches. The results obtained are; The basic longline fishing gear consists of a main rope of 10,000 m long, 30 cm branch rope, swivel, 2,000 cork buoys, stone weights weighing 5-8 kg, and fishing hooks of 10,000 seeds. The operating method of basic longline fishing gear consists of setting, and hauling. The financials of the basic longline catching business at TPI Hamadi show that the fishing business is feasible. The feasibility of basic longline catching business can be seen with the NPV value of 7,154,663 (NPV> 0), IRR 24% (IRR > 19%), Payback Period is 2.28 (PP < 3 years) including the fast return category, and the B/C Ratio is 1,19 (B/C > 1), so it can be concluded that the basic longline fishery business is declared financially feasible. Key Words: Net Present Value; Internal Rate of Return; Payback Period; Benefit Cost Ratio; TPI Hamadi